The study of the main phenological phases and the compilation of the calendar for the collection of medicinal plants of the Bukhar-Zhyrau district of the Karaganda region - Auelbekova, A.K.; Kyzdarova, D.K.; Atikeeva, S.N.; Aidarbaeva, D.K.; Karimtaeva, T.N. (Fundamental and Experimental Biology, 2018)
The results of phenological investigation of 39 species of medicinal plants of Bukhar-Zhirau district of Karaganda region mountains are presented. According to botanical-geographical zoning classification, the vegetation of Bukhar-Zhirau district of Karaganda region mountains belongs to Kopalisky area of Central Kazakhstan sub province. Establishment phase collection of raw material medicines plants over several years allowed by experiment to establish the optimal time for the collection of raw materials of medicinal plants Bukhar-Zhirau district of Karaganda region mountains allowing for the local climate. It was revealed that for the preparation of 6 species of medicinal plants (patrini medium, medicinal herb, iris leathery, Dzungarian ferula and others), underground organs are prepared on the territory of Bukhar-Zhyrau district of the Karaganda region. For 1 species, the dogrose is loose, fruit is collected. For 23 witches, such as donut whiteness, donutic dipstick, serpuhus, venous pumpkin, saussurea salsa, ziziphora peach and other, the production of grass is produced. For other species harvest leaves, shoots and flower baskets are harvested. Phonological spectra for 33 species of medicinal plants of Bukhar-Zhyrau district were compiled on the basis of which a calendar was compiled and the frequency of collection of plant raw materials during the growing season was determined. The basic rules for organizing the preparation and drying of medicinal plant raw materials are determined. The data by phonological spectra let us to create the schedule and periods of the gathering of the raw material. The results of the work are the base for the organization of plan exploitation of the natural populations.